2013
DOI: 10.4236/am.2013.47137
|View full text |Cite
|
Sign up to set email alerts
|

Hyers-Ulam-Rassias Stability for the Heat Equation

Abstract: In this paper we apply the Fourier transform to prove the Hyers-Ulam-Rassias stability for one dimensional heat equation on an infinite rod. Further, the paper investigates the stability of heat equation in with initial condition, in the sense of Hyers-Ulam-Rassias. We have also used Laplace transform to establish the modified Hyers-Ulam-Rassias stability of initial-boundary value problem for heat equation on a finite rod. Some illustrative examples are given. n 

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Afterward Gila´ny [7] showed that is if satisfies the functional inequality f satisfies the Jordan-von Newman functional equation Then, mathematicians in the world proved to extend the functional inequality (1.11) as [7]- [17].In addition, mathematicians have developed the achievements of their predecessors who have built mathematical models from advanced to modern mathematics, especially functional equations applied on function spaces to Unlocking means connecting with other Maths. [3]- [35]Recently, the authors studied the Hyers-Ulam-Rassias type stability for the following functional inequalities (see [31], [32], [34])…”
Section: Introductionmentioning
confidence: 99%
“…Afterward Gila´ny [7] showed that is if satisfies the functional inequality f satisfies the Jordan-von Newman functional equation Then, mathematicians in the world proved to extend the functional inequality (1.11) as [7]- [17].In addition, mathematicians have developed the achievements of their predecessors who have built mathematical models from advanced to modern mathematics, especially functional equations applied on function spaces to Unlocking means connecting with other Maths. [3]- [35]Recently, the authors studied the Hyers-Ulam-Rassias type stability for the following functional inequalities (see [31], [32], [34])…”
Section: Introductionmentioning
confidence: 99%
“…In [27], M. N. Qarawani used the Laplace transform to establish the Hyers-Ulam-Rassias-Gavruta stability of initial-boundary value problem for heat equations on a finite rod:…”
Section: Introductionmentioning
confidence: 99%